Attitude toward food waste reduction: the case of Italian consumers. (2017) - Fiore, Mariantonietta; Pellegrini, Giustina; Sala, Piermichele La; Conte, Alessandra; Liu, Bin
This study aimed to investigate the dynamics of household food waste by analysing Italian consumer behaviour. Specifically, the study tried to find the determining factors of household food waste and the main consumer motivations that may lead to reduction of food waste. In order to reach this goal, an online survey was carried out through a web-based questionnaire. Data analysis were conducted in the following steps: (1) a descriptive statistical analysis for illustrating the sample; (2) a correlation analysis followed by principal component analysis (PCA). Results show that consumers are aware of the environmental and economic impacts of food waste, although waste continues to occur at household level. The authors suggest that interventions should be taken to influence consumers' choices related to purchasing and consuming food, such as changing their planning and shopping routines. For policy makers and social marketers, the results implicate the crucial importance of avoiding food-related habits in consumers' lives.